Relative Greenhouse Gas Abatement Cost Competitiveness of Biofuels in Germany - Markus Millinger; Kathleen Meisel; Maik Budzinski; Daniela Thrän (Energies, 2018)
Transport biofuels derived from biogenic material are used for substituting fossil fuels, thereby abating greenhouse gas (GHG) emissions. Numerous competing conversion options exist to produce biofuels, with differing GHG emissions and costs. In this paper, the analysis and modeling of the long-term development of GHG abatement and relative GHG abatement cost competitiveness between crop-based biofuels in Germany are carried out. Presently dominant conventional biofuels and advanced liquid biofuels were found not to be competitive compared to the substantially higher yielding options available: sugar beet-based ethanol for the short- to medium-term least-cost option and substitute natural gas (SNG) for the medium to long term. The competitiveness of SNG was found to depend highly on the emissions development of the power mix. Silage maize-based biomethane was found competitive on a land area basis, but not on an energetic basis. Due to land limitations, as well as cost and GHG uncertainty, a stronger focus on the land use of crop-based biofuels should be laid out in policy.